Affordability of residential house rent market value in Hawassa city - Aschale Mekuria Shitaye (Cogent Economics & Finance, 2022)
The urban housing situation in Ethiopia is a wide gap between housing demand and actual supply in all urban centers of the country. Generally, the study aims to examine the affordability of residential house rent market value. Specifically, the study aims to assess the characteristics of rental housing, examined rent affordability; identify factors that determined rental affordability in Hawassa city, Sidama Regional State, Ethiopia. The study employed both primary and secondary data. Primary data were obtained from 219 rental households through questioners. For data analysis, the study employed both descriptive and inferential statistics. Logistics regression estimation technique was used to examine the affordability of residential house rent market value. About 68.04% of surveyed households were paid 30% or less of their monthly income to residential house rent, and 31.96% of a household were spent more than the thresholds' income level. The findings of the study revealed that household income, marital status, number of rooms, transport access and house typology are the determinants of residential house rent market value affordability in Hawassa city, Sidama region, Ethiopia. The study suggests that government should be focused on constructing public houses, controlling the effects of illegal brokers and subsidizes private house builders through credit access, tax break down for imported construction materials and provision of land with low lease.
Keywords: 330; Residential house; rent value; affordability; logistic regression; Hawassa